Reintroduksi Hukum Islam dalam Wacana Kebangsaan - Cipto Sembodo (Universitas Islam Indonesia, 2008)
This article discusses a discourse of Islamic Law in the context of nationality. This focuseson some efforts to bring Islamic Law back in to a system and regulatory pattern ofa pluralistic modern society, socially and culturally. This is inspired by the current phenomenonthat there has been an increased appreciation of society on Islamic Law significantly.This article argues that it is necessary to reintroduce Islamic Law in a discourse of nationality,and therefore, every product of Islamic Law thought should be able to positivelyinteract with the system of power and politics.Keywords: Islamic Law, nationality, reintroduce, power and politics.